If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -18 = 3(2y + -4) Reorder the terms: -18 + 4y = 3(2y + -4) Reorder the terms: -18 + 4y = 3(-4 + 2y) -18 + 4y = (-4 * 3 + 2y * 3) -18 + 4y = (-12 + 6y) Solving -18 + 4y = -12 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -18 + 4y + -6y = -12 + 6y + -6y Combine like terms: 4y + -6y = -2y -18 + -2y = -12 + 6y + -6y Combine like terms: 6y + -6y = 0 -18 + -2y = -12 + 0 -18 + -2y = -12 Add '18' to each side of the equation. -18 + 18 + -2y = -12 + 18 Combine like terms: -18 + 18 = 0 0 + -2y = -12 + 18 -2y = -12 + 18 Combine like terms: -12 + 18 = 6 -2y = 6 Divide each side by '-2'. y = -3 Simplifying y = -3
| d/dx(sin(2)x) | | -5(10)+7y=-15 | | 3x=-7+y | | 6y-4y=16+2y | | (6x-5)+8=2(x-5) | | x^2-1/81=0 | | t^3-5t^2+3t=0 | | 6-4y=16+2y | | 1/3x=-2/5=-6/5 | | -200-x=103/2x | | 6x-4y=16+2y | | 8x-3=2x+10 | | 4(2y-3)+6(3-y)=22 | | 17+4x-1x= | | -5+7y=-15 | | 4x=x-32 | | 12x=9x-12 | | 3(1-1y)=24-1y | | 3(3x-2)=7x+4 | | 5=6+a | | 5x+24x= | | 4x-3=2x+10 | | 48=3(x+8) | | y-3=-9 | | 5(7x+5)=130 | | 6x+3y=24+1y | | 5x-2(-8)=6 | | 6=u+9 | | 2a+18=5a+6 | | 7(7x-9)=67x+7v*8x | | 2x+2y+1+6y+x-6=180 | | 1/3x=-2/5 |